Doxorubicin induces cardiotoxicity in a pluripotent stem cell model of aggressive B cell lymphoma cancer patients - Haupt, Luis Peter; Rebs, Sabine; Maurer, Wiebke; Hübscher, Daniela; Tiburcy, Malte; Pabel, Steffen; Maus, Andreas; Köhne, Steffen; Tappu, Rewati; Haas, Jan; Li, Yun; Sasse, Andre; et al. (Basic research in cardiology, 2022)
Cancer therapies with anthracyclines have been shown to induce cardiovascular complications. The aims of this study were to establish an in vitro induced pluripotent stem cell model (iPSC) of anthracycline-induced cardiotoxicity (ACT) from patients with an aggressive form of B-cell lymphoma and to examine whether doxorubicin (DOX)-treated ACT-iPSC cardiomyocytes (CM) can recapitulate the clinical features exhibited by patients, and thus help uncover a DOX-dependent pathomechanism. ACT-iPSC CM generated from individuals with CD20+ B-cell lymphoma who had received high doses of DOX and suffered cardiac dysfunction were studied and compared to control-iPSC CM from cancer survivors without cardiac symptoms. In cellular studies, ACT-iPSC CM were persistently more susceptible to DOX toxicity including augmented disorganized myofilament structure, changed mitochondrial shape, and increased apoptotic events. Consistently, ACT-iPSC CM and cardiac fibroblasts isolated from fibrotic human ACT myocardium exhibited higher DOX-dependent reactive oxygen species. In functional studies, Ca2+ transient amplitude of ACT-iPSC CM was reduced compared to control cells, and diastolic sarcoplasmic reticulum Ca2+ leak was DOX-dependently increased. This could be explained by overactive CaMKIIδ in ACT CM. Together with DOX-dependent augmented proarrhythmic cellular triggers and prolonged action potentials in ACT CM, this suggests a cellular link to arrhythmogenic events and contractile dysfunction especially found in ACT engineered human myocardium. CamKIIδ inhibition prevented proarrhythmic triggers in ACT. In contrast, control CM upregulated SERCA2a expression in a DOX-dependent manner, possibly to avoid heart failure conditions. In conclusion, we developed the first human patient-specific stem cell model of DOX-induced cardiac dysfunction from patients with B-cell lymphoma. Our results suggest that DOX-induced stress resulted in arrhythmogenic events associated with contractile dysfunction and finally in heart failure after persistent stress activation in ACT patients.